1997
DOI: 10.1103/physrevb.56.7574
|View full text |Cite
|
Sign up to set email alerts
|

Optical spin resonance and transverse spin relaxation in magnetic semiconductor quantum wells

Abstract: Ultrafast optical pulses are used to initiate and measure free-induction decays of coherent conduction electron spins and of embedded magnetic Mn 2ϩ ions in a series of magnetic-semiconductor quantum wells. These time-resolved Faraday rotation experiments in transverse applied magnetic fields complement previous studies of spin dynamics in longitudinal fields by unambiguously distinguishing between the spin relaxation of electrons and holes, and by identifying a mechanism by which angular momentum is transferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
246
4
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(262 citation statements)
references
References 40 publications
10
246
4
2
Order By: Relevance
“…84 Spin relaxation has also been investigated in In/GaAs (Paillard et al, 2001;Cortez et al, 2002), in an InAs/ GaSb superlattice , in InGaAs (Guettler et al, 1998), in GaAsSb multiple quantum wells . II-VI quantum wells, specifically ZnCdSe, were studied by Kikkawa et al (1997), who found s Ϸ1 ns, weakly dependent on both mobility and temperature, in the range 5ϽTϽ270 K. Electron and hole spin dephasing have also been investigated in dilute magnetic semiconductor quantum wells doped with Mn ions (Crooker et al, 1997;Camilleri et al, 2001).…”
Section: Low-dimensional Semiconductor Structuresmentioning
confidence: 99%
“…84 Spin relaxation has also been investigated in In/GaAs (Paillard et al, 2001;Cortez et al, 2002), in an InAs/ GaSb superlattice , in InGaAs (Guettler et al, 1998), in GaAsSb multiple quantum wells . II-VI quantum wells, specifically ZnCdSe, were studied by Kikkawa et al (1997), who found s Ϸ1 ns, weakly dependent on both mobility and temperature, in the range 5ϽTϽ270 K. Electron and hole spin dephasing have also been investigated in dilute magnetic semiconductor quantum wells doped with Mn ions (Crooker et al, 1997;Camilleri et al, 2001).…”
Section: Low-dimensional Semiconductor Structuresmentioning
confidence: 99%
“…For the GaAs (100) surface we observe an increase from about 60 ps to 1600 ps over an energy range of more than 0.3 eV, whereas the spin-relaxation time for the (011) surface is about 60 ps, independent of energy. The bulk spin relaxation was measured on an identical sample by means of the time-resolved magnetooptical Faraday effect [16,17]. The bulk spin-relaxation time was found to be 60 ps at room temperature regardless of the crystal orientation and is also shown in Figure 4 as a guide to the eye.…”
mentioning
confidence: 99%
“…We attribute this to the spin relaxation of the photoexcited holes, which lose their initial spin orientation very fast. 21 Here we don't consider this fast decay, i.e., hole spin relaxation. Figure 2(a) shows TRKR traces under a magnetic field of 0.5 T at different temperatures of 4 K, 14 K, and 16 K. One can find that the oscillatory envelope decay becomes much slower from 4 K to 14 K, and a little faster from 14 K to 16 K [see the inset of Fig.…”
mentioning
confidence: 99%